STRATEGI SUKSES MAHASISWA INDONESIA MERAIH KARIR GEMILANG DENGAN SOFT SKILL - Heri Kuswara (Universitas Bina Sarana Informatika, 2010)
In some opportunities, the writer tries to ask to working environment about the eweakness of local universities graduates if we compare with overseas universities graduates, almost all working environment reply the weakness of local product is lack of self confidence, lack of communication skill (particularly when havingf presentation in front of many people), lack of adaptation skill (colud not socialize with many people from many bacgrounds) and lack of facing pressures (challenges or job matters). From above answer. We can conclude that even though from hard skill those local graduates are able to compete however from soft skill, they are still left behind from overseas products. Through this media, the writer tries to give various solutions to all college students in Indonesian Universities to motivate and soon commensurate themselves with overseas products so that everyone are able to be the winner in human resoruces competition in global stage. Keywords: Product, Soft Skill, Student